Stabilisation of hepatocyte phenotype using synthetic materials - Lucendo Villarin, Baltasar (The University of Edinburgh, 2016)
Primary human hepatocytes are a scare resource with limited lifespan and variable function which diminishes with time in culture. As a consequence, their use in tissue modelling and therapy is restricted. Human embryonic stem cells (hESC) could provide a stable source of human tissue due to their self-renewal properties and their ability to give rise to all the cell types of the human body. Therefore, hESC have the potential to provide an unlimited supply of hepatocytes. To date, the use of hESCs-derived somatic cells is limited due to the undefined, variable and xeno-containing microenvironment that influences the cell performance and life span, limiting scale-up and downstream application. Therefore, the development of highly defined cell based systems is required if the true potential of stem cell derived hepatocytes is to be realised. In order to replace the use of animal derived culture substrates to differentiate and maintain hESCs-derived hepatocytes, an interdisciplinary approach was employed to define synthetic materials, which maintain hepatocyte-like cell phenotype in culture. A simple polyurethane, PU134, was identified which improved hepatocyte performance and stability when compared to biological matrices. Moreover, the synthetic polymer was amenable to scale up and demonstrated batch-to-batch consistency. I subsequently used the synthetic polymer surface to probe the underlying biology, identifying key modulators of hepatocyte-like cell phenotype. This resulted in the identification of a novel genetic signature, MMP13, CTNND2 and THBS2, which was associated with stable hepatocyte performance. Importantly, those findings could be translated to two hESC lines derived at GMP. In conclusion, hepatocyte differentiation of pluripotent stem cells requires a defined microenvironment. The novel gene signature identified in this study represents an example of how to deliver stable hESCs-derived hepatocytes.
Keywords: hESC; hepatocytes; PU134; synthetic substrate; phenotypic stability